Issues in the Science and Engineering Education in Indonesia: How to Improve Competitiveness Through STEM Mastery - Veza, Ibham; Muhamad Said, Mohd Farid; Riyadi, Tri Widodo Besar; Abas, Mohd Azman; Abdul Latiff, Zulkarnain (International Journal of Advanced Research in Future Ready Learning and Education, 2021)
The rapid advancement of technology and information in Indonesia over the last few decades has provided great benefits to all around its citizen. However, this is not accompanied by the availability of skilled workers in the fields of Science, Technology, Engineering, and Mathematics or what is more commonly abbreviated as STEM. Countries such as the United States have taken rapid steps to reduce the human resource deficit of Pam Sam's country with various incentives in the STEM field. Unmitigated, America opened more than one million new job openings in 2018, the majority (71%) of which were STEM-related jobs. This essay will discuss the urgency of mastering STEM aspects in Indonesia. Several case studies from several developed countries will be provided. In addition, suggestions for the development of STEM that can be done by the government will also be presented in this essay.